Better utilization of crop residues and by-products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Towards optimal feeding of agricultural by-products to livestock in Africa / ARNAB. (1986). Proceedings of a workshop held at the University of Alexandria, Egypt, October 1985. African Research Network for Agricultural Byproducts (ARNAB), ILCA, Addis Abab